ANALISIS KUALITAS AIR LAUT UNTUK PENENTUAN LOKASI BUDIDAYA KERAPU BEBEK MENGGUNAKAN CITRA SATELIT LANDSAT-8 (Studi Kasus : Teluk Lampung, Lampung) - Jaelani, Lalu Muhamad; Kartikasari, Fitriana; Winarso, Gathot (Departemen Teknik Geomatika ITS, 2016)
Cromileptes Altivelis is one kind of exported fish commodities which are common in some areas of Indonesia. It cultured using Keramba Jaring Apung (KJA). Lampung Bay is one of the waters area that have potential as a location for the cultivation of those fishs. Determination of location for Cromileptes Altivelis aquaculture activities has strongly influenced by the quality of water because it affects the metabolism of fish growth. Described in the Standar Nasional Indonesia (SNI) 6487.4:2011 on Enlargement Production Cromileptes Altivelis in Keramba Jaring Apung (KJA) where the salinity, sea surface temperature, and pH are the important parameters that can affect the quality of sea water. In this research, the method that used to determine the location of CromileptesAltivelis aquaculture was remote sensing using Landsat-8 satellite imagery. This was because the Landsat-8 could work at visible wave (visible spectrum) where there are channels that can be used to extract quality parameters of ocean water. In determining the concentration of sea water quality parameters, this research used Son, et al algorithm and Syariz, et al algorithm to determine the value of salinity and sea surface temperature.Condition of water quality parameters in the Bay of Lampung was quite in accordance with the limit values listed in SNI 6487.4:2011 to be location of CromileptesAltivelis. Dominance value of sea surface temperature distribution was 26.05-30.05 C, dominance value of salinity distribution was 31.40-39.25 psu, and dominance value of pH distribution was 7.00–13.99. Based on the analysis of sea water quality parameters in Lampung Bay, territorial waters obtained 85.171,76 ha area corresponding to the location of Cromileptes Altivelis aquaculture.